LUNAR HIGHLAND METEORITE DHOFAR 026 AND APOLLO SAMPLE 15418: TWO STRONGLY SHOCKED, PARTIALLY MELTED, GRANULITIC BRECCIAS - Cohen B.A.; Taylor L.A.; James O.B.; Nazarov M.A.; Barsukova L.D. (My University, 2004)
Studies of lunar meteorite Dhofar 026, and comparison to Apollo sample 15418, indicate that Dhofar 026 is a strongly shocked granulitic breccia (or a fragmental breccia consisting almost entirely of granulitic breccia clasts) that experienced considerable post‐shock heating, probably as a result of diffusion of heat into the rock from an external, hotter source. The shock converted plagioclase to maskelynite, indicating that the shock pressure was between 30 and 45 GPa. The post‐shock heating raised the rock's temperature to about 1200 °C; as a result, the maskelynite devitrified, and extensive partial melting took place. The melting was concentrated in pyroxene‐rich areas; all pyroxene melted. As the rock cooled, the partial melts crystallized with fine‐grained, subophitic‐poikilitic textures. Sample 15418 is a strongly shocked granulitic breccia that had a similar history, but evidence for this history is better preserved than in Dhofar 026. The fact that Dhofar 026 was previously interpreted as an impact melt breccia underscores the importance of detailed petrographic study in interpretation of lunar rocks that have complex textures. The name “impact melt” has, in past studies, been applied only to rocks in which the melt fraction formed by shock‐induced total fusion. Recently, however, this name has also been applied to rocks containing melt formed by heating of the rocks by conductive heat transfer, assuming that impact is the ultimate source of the heat. We urge that the name “impact melt” be restricted to rocks in which the bulk of the melt formed by shock-induced fusion to avoid confusion engendered by applying the same name to rocks melted by different processes.